2020
DOI: 10.7759/cureus.6539
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Radiographic Fractal Analysis at Implant Recipient Sites with Primary Implant Stability: An In Vivo Preliminary Study

Abstract: The aim of this study was to demonstrate a possible correlation between radiographic trabecular bone quantified with fractal dimensions analysis and values of primary implant stability deliberated using the Osstell ® monitor (Integration Diagnostics AB, Goteborgsvagen, Sweden) with the density of bone specimens harvested from the implant recipient sites and calculated using the mass and volume of the bone bloc specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Some studies report that radiographic settings such as kVp, mAs and X-ray angulation may have a minimal effect on the FD (White & Rudolph 1999, Jolley et al 2006. Other studies have indicated that FD values are not affected by contrast, tube angulation and irradiation on the images obtained of acceptable clinical standard (Hayek et al 2020). In addition, during the early healing period, using fractal analysis periapical trabecular pattern changes can be detected, and improvements can be evaluated with numerical data (Chen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that radiographic settings such as kVp, mAs and X-ray angulation may have a minimal effect on the FD (White & Rudolph 1999, Jolley et al 2006. Other studies have indicated that FD values are not affected by contrast, tube angulation and irradiation on the images obtained of acceptable clinical standard (Hayek et al 2020). In addition, during the early healing period, using fractal analysis periapical trabecular pattern changes can be detected, and improvements can be evaluated with numerical data (Chen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hayek et al compared the fractal dimension value of the pre-implant bone with the histological density of the extracted bone block during implant placement. They stated that as the fractal dimension increased, the bone density increased as well [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are many studies evaluating changes in trabeculation as a result of early loading, bone quality, peri-implantitis areas and primary stability of the implant using methods such as fractal dimensional analysis, MCI evaluation and resonance frequency analysis ( Hayek et al, 2020 ; Lee et al, 2010 ; Friberg et al, 1999 ). However, there are few studies investigating whether there is a correlation between pre- and post-operative trabecular pattern with MCI and MCW ( Bayrak et al, 2020 ; Ersu, Akyol & Etöz, 2021 ).…”
Section: Discussionmentioning
confidence: 99%